Pengaruh Personal Branding Vincent Desta dan Guerilla Marketing terhadap Brand Image: Studi Kasus Instagram Vindes Store - Aulia Zahra; Adam Hermawan; Btari Mariska Purwaamijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of Vincent Desta's personal branding by looking at the concept of guerilla marketing as a marketing element on the brand image on the Vindes Store Instagram. This research data was obtained from the results of distributing questionnaires with a population sample of 190 respondents processed using SPSS. The findings of this research show that there is a positive influence of the personal branding variable on brand image partially, the guerilla marketing variable also has a positive influence on brand image partially, the personal branding and guerilla marketing variables have a simultaneous influence on brand image with an R - Square value amounting to 14.7% with the variability of brand image being explained by personal branding and guerilla marketing.